Coulson & Richardson's chemical engineering. Vol. 6, - Sinnott, R. K. (Elsevier Butterworth-Heinemann, 2005)
Coulson and Richardson's classic series provides the student with an account of the fundamentals of chemical engineering. This volume covers the application of chemical engineering principles to the design of chemical processes and equipment.